Edukasi Trading Sebagai Upaya Peningkatan Kemandirian Finansial untuk Ibu Rumah Tangga : Penelitian - Viamali Natania Firmansyah; Zawawi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The futures and commodity trading industry is currently showing rapid growth year after year. Futures trading can actually be carried out by various groups, including housewives, but currently not many housewives know what trading is. To increase awareness and understanding among the wider community, especially housewives, an educational program entitled “100 thousand rupiah in the right hands” was created. This activity aims to increase financial independence for housewives and is carried out through a two-way communication approach, which includes presentation and question and answer sessions. The success indicators for this activity are that the audience demonstrates an understanding of the concept of trading, actively asks questions, and shows enthusiasm. This program is also conducted to build good relationships with housewives who may be interested in the world of trading.